1985
DOI: 10.1021/jo00224a058
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-promoted aqueous decomposition of Aldicarb

Abstract: iV-acetylpiperonylamine, 98799-34-9; vanillin, 121-33-5; 4-iso-propoxybenzaldehyde, 2538-98-9; 3-methoxy-4-isopropoxybenzaldoxime, 98799-36-1; 3-methoxy-4-isopropoxybenzylamine, 98799-37-2; 3-methoxy-4-isopropoxy-Ñ-acetylbenzylamine, 98799-38-3; 2-iodo-5-methoxy-4-isopropoxy-N-acetylbenzylamine, 98799-39-4; 3,4,5-trimethoxybenzoic acid, 118-41-2; piperonaldehyde, 120-57-0; veratraldehyde, 120-14-9; isovanillin, 621-59-0. Supplementary Material Available:NMR spectral data for 3a-p, 4a-p, 13a,c, 14a-c, and 15a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

1986
1986
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…However, the rate of degradation is significantly faster than in Cu II -free solutions of the same composition (a significant difference is apparent when reactions are monitored for three months). These findings are consistent with earlier studies that attribute Cu II -facilitated degradation of oxamyl and related carbamates to metal ion catalysis of the E1cb reaction (9,33).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…However, the rate of degradation is significantly faster than in Cu II -free solutions of the same composition (a significant difference is apparent when reactions are monitored for three months). These findings are consistent with earlier studies that attribute Cu II -facilitated degradation of oxamyl and related carbamates to metal ion catalysis of the E1cb reaction (9,33).…”
Section: Resultssupporting
confidence: 93%
“…No direct evidence for the role of metal ion-carbamate coordination was obtained in this study. We expect that any bonding between Fe II and Lewis base groups present on the carbamates would be weak and difficult to detect by spectroscopic methods (33). Indirect evidence, however, indicates that metal ion coordination is not an essential component of the reaction mechanism.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Let us return now to the observation that Fe II species in which five or six coordination positions are occupied by the organic ligand exhibit less reactivity than the LFER would predict. Metal ion coordination is believed to be an important factor in the metal ion-catalyzed hydrolysis of oxime esters ( ), and oxamyl possesses several Lewis base groups capable of coordinating Fe II ( , ). We can therefore postulate that outer-sphere Fe II -to-oxamyl electron transfer is significantly slower than electron transfer within an Fe II −oxamyl inner-sphere complex.…”
Section: Resultsmentioning
confidence: 99%
“…No significant increases in the hydrolysis rates for aldicarb sulfoxide and aldicarb sulfone were observed. Bank and Tyrrell [21] reported that cuprous and zinc ions catalyze the hydrolysis of aldicarb in distilled water solutions and, as mentioned earlier, Bromilow showed that ferrous ions also catalyze the hydrolysis of aldicarb…”
Section: Distilled Water Hydrolysis Repeatability Testsmentioning
confidence: 64%